2006
DOI: 10.1098/rstb.2006.1937
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurophysiological evidence for face identity and face emotion processing in animals

Abstract: Visual cues from faces provide important social information relating to individual identity, sexual attraction and emotional state. Behavioural and neurophysiological studies on both monkeys and sheep have shown that specialized skills and neural systems for processing these complex cues to guide behaviour have evolved in a number of mammals and are not present exclusively in humans. Indeed, there are remarkable similarities in the ways that faces are processed by the brain in humans and other mammalian specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 115 publications
(150 reference statements)
5
150
0
7
Order By: Relevance
“…Consider a parallel evolved system for communicating individual identity: visual face recognition. There is now considerable evidence that humans, other primates and even sheep are able to recognize individuals by distinctive visual characteristics of their faces (reviewed in Calder & Young 2005;Tate et al 2006;McKone et al 2007). This ability seems to reside in some sort of holistic processing of relational visual information.…”
Section: Discussionmentioning
confidence: 99%
“…Consider a parallel evolved system for communicating individual identity: visual face recognition. There is now considerable evidence that humans, other primates and even sheep are able to recognize individuals by distinctive visual characteristics of their faces (reviewed in Calder & Young 2005;Tate et al 2006;McKone et al 2007). This ability seems to reside in some sort of holistic processing of relational visual information.…”
Section: Discussionmentioning
confidence: 99%
“…This network of brain regions that perceive and analyze faces is informed by ventral and dorsal visual pathways-the ventral enabling fine discrimination and the dorsal providing rapid, but coarse, emotional assessment (3). Brain mapping investigations on other species capable of human recognition are extremely limited; however, electrophysiological recordings in the visual cortex of domestic sheep and nonhuman primates have indicated the presence of neurons that respond to human facial information (5).…”
mentioning
confidence: 99%
“…Sheep are social animals that readily recognize faces and interpret facial expressions of their conspecifics, even when the faces presented on a computer monitor. Single-unit electrophysiological recordings have revealed that neurons in the sheep temporal cortex exhibit selectivity for faces that bears a striking similarity to that observed in monkeys and humans (Tate, Fischer, Leigh, & Kendrick, 2006). While this observation does not imply that sheep possess a human-like potential for mind reading, it does at least raise the question whether the sheep homologs of the human STS and TPJ might be involved in some form of social monitoring.…”
Section: * * *mentioning
confidence: 85%